The Analysis of Raw Material Usage Based on Forecast System - Andy Febrianto; Ngatimin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to prove that a raw material forecasting system is capable of predicting future demand for raw materials based on historical data and external factors such as market trends, seasons, economic conditions, and so on. By predicting the demand for raw materials, companies can make better production planning and avoid raw material shortages that can affect the production and quality of the final product. The research was conducted at PT. Muara Juara Kreasi Indonesia. Data analysis used descriptive qualitative. The results showed that the procedure for using raw materials at PT. Muara Juara Kreasi Indonesia was quite well done. Raw material inventory storage, raw material requests, raw material recording is quite good and easy to find when needed. Furthermore, by using a raw material forecasting system, the effectiveness of using raw materials at PT. Muara Juara Kreasi Indonesia is quite good, but the instability of sales due to the pandemic makes predictions still less accurate.